PENERAPAN TEKNOLOGI PRODUKSI SIMPLISIA EMPON-EMPON, KELOMPOK TANI KECAMATAN TRAWAS, KABUPATEN MOJOKERTO, JAWA TIMUR - Anggarani, Mirwa; Purnama, Erlix Rakhmad; Sulistyowati, Raya (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
The community service aims to solve several main problems experienced by empon-empon farmers,namely the limited knowledge of the production techniques of empon-empon simplisia and the productionfacilities of empon-empon simplisia. These problems are experienced by partner "Gunung Jambe" SMEs,trawas sub-district, Mojokerto regency, East Java. To achieve the objectives of the PKM program, it isnecessary to introduce science and technology regarding: (1) optimizing the manufacture of export qualitysimons (SNI: 01-3393-1994); (2) analysis of the nutritional content of simplicia empon-empon; (3) analysisof shelf life of empon-empon simplicia products. The implementation of PKM activities was carried outbetween May and September 2019. Based on the analysis of the nutritional content of the empon-emponsimplicia product, it is known that the simplicia empon-empon contains 1.54% water; ash 9.45%;carbohydrates 86.70%; fat 0.91%; and protein 1.41%. From the results of the implementation of PKM inJune 2019, there was very high enthusiasm from PKM participants. In addition, there were some inputsfrom the trainees related to the next activity which were conveyed through the trainee questionnaire.